The Efficacy of Staff members' Work Performance at Northern Finance College Luang Prabang Province: https://doi.org/10.69692/SUJMRD100474 - Many, Sommay; Keoboualapheth , Soulideth; Pimpisan, Thavyxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research were 1) to study the performance efficiency of the Northern Finance College, 2) to study the motivation of staff members' work the Northern Finance College, 3) Analyze the relationship between motivation factors in work performance and work performance efficiency of employees of Northern Finance College, Luang Prabang Province, and 4) to study the factors affecting the working efficiency of the Northern Finance College. The sample group was 47 people from the Northern Finance College. The questionnaire was used as a tool for collecting the data. The data collected was analyzed by using the frequency, percentage, mean and standard deviation. This was used to test the hypothesis for each pair in order to see which pair was different with Multiple Regression Analysis. The results of the research found that the work efficiency of the employees of the Northern Finance College in Luang Prabang province is generally very good, such as the quantity of work, the quality of work and the time. The motivation to perform the work as a whole has many levels of motivation, in which the most motivation is the success in work, followed by the creative and challenging nature of the work and the least motivation is the advancement in the career. The relationship between the motivation factor in work performance and the performance of employees of the Northern Finance University in Luang Prabang Province is related in the same direction which is the motivation for success in high work, motivation from receiving respect, motivation from career advancement, from the work environment and from work responsibility. The motivation factor for work performance is the success factor in work and the responsibility factor in work has an effect on the work efficiency of the staff of Northern Finance College in Luang Prabang province.